Pembangunan modul kimia UM berasaskan pengetahuan pedagogi kandungan (PPK) bagi topic ikatan kimia - Selamat, Minah (2014)
This study aims to develop teaching modules for the basic concepts of chemical bonding based on knowledge Pedagogical Content (PCK). This study also investigated the effectiveness of the UM Chemical Module that has been built. However, to achieve these objectives, student`s understanding before and after exposure to the UM Chemical Module was identified. This descriptive study involved thirty students at school in Kota Tinggi, Johor. Data collection was done through testing. Score test and content analysis were analyzed using frequency, percentage and mean. This study found that majority of the students is difficult to distinguish between ionic and covalent bond, to explain the formation of ionic and covalent bonding, to draw the diagram of ionic and covalent bond and to write chemical formulas. Construction of UM Chemical Module has considered the questions that are found in the CoRe. Teaching strategies used in this module are inquiry approach and hands on activities. The results of exposure of students to the use of UM Chemical Module has managed to increase student`s understanding in chemical bond